Antiproliferative Potential of Biosynthesized Gold Nanoparticles in HepG2 Liver Cancer Cells - Muzammal Mateen Azhar; Tahir Maqbool; Afsheen Akbar; Maryam Raza; Syedda Amina Rizvi; Fatima Ali (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To assess the anticancer potential of biologically synthesized gold nanoparticles (AuNPs) through in vitro evaluation, elucidate their antiproliferative mechanisms, and examine their effects on the Hep G2 cell line. METHODOLOGY: Gold nanoparticles (AuNPs) were biologically synthesized using the fungus Aspergillus terreus at the Microbiology Lab, IMBB Department, The University of Lahore. These nanoparticles were characterized to determine their size using X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM). The IC50 of the synthesized AuNPs was evaluated using the MTT assay, which measures cell viability. A scratch assay was performed to assess wound-healing capacity. Additionally, gene expression was analysed by quantitative polymerase chain reaction (qPCR) to investigate the molecular mechanisms underlying the antiproliferative effects of AuNPs in the HepG2 liver cancer cell line. RESULTS: X-ray diffraction (XRD) analysis revealed gold nanoparticles (AuNPs) with a size range of 18 ± 29 nm, while Transmission Electron Microscopy (TEM) measured them at 13 ± 8 nm. The AuNPs demonstrated significant anticancer activity against the Hep G2 cell line, as evidenced by cytotoxicity assays and qPCR analysis of altered gene expression patterns. CONCLUSION: Biologically synthesized gold nanoparticles exhibit potent anticancer effects, suggesting their potential as an alternative therapeutic approach for liver cancer. Further investigations are necessary to elucidate their precise mechanisms of action and assess their clinical applicability.